Использование биоцидных воздействий для борьбы с возбудителями микробиологической коррозии бетона в трубопроводах водоотведения - Юрченко, Валентина Александровна; Петков, Александр Александрович; Бригада, Елена Владимировна (Одесский национальный университет им. И. И. Мечникова, 2001)
Исследовано влияние химических и физических биоцидных воздействий на микробиоценоз тионовых бактерий-возбудителей коррозии бетона в сетях водоотведения. Установлено, что тионовые бактерии обладают чрезвычайно высокой, по сравнению с сапрофитами, устойчивостью к действию химических биоцидов и физических биоцидных факторов.

The results of experimental researches say about high resistance of rich culture of tionic bacteria, immobilizing on a concrete, for chemical and physical biocide influences. For the operation safety of biological treatment constructions in the sewer-pipes is better to carry out using physical biocide factors - ultra-violet radiation. The chemical biocides are desirable introduced only on arch part of pipelines.
Using of biocide influences for fighting with microbial concrete corrosion of the sewer-pipes
Keywords: химические биоциды; УФ-излучение; кислотообразование; тионовые бактерии; chemical biocides; UV-radiation; acid formation; tionic bacteria